PENGEMBANGAN E-BOOK BERBASIS MULTIMEDIA PADA PEMBELAJARAN IPA KELAS VIII SESUAI DENGAN GAYA BELAJAR PESERTA DIDIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR - Anes Fitria (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
This study aims to reveal: how is the process of developing multimedia-based e-books on learning natural science (IPA) valid ?, how is the practicality of multimedia-based e-books on science learning ?, how is the effectiveness of developing multimedia-based e-books on science learning? . the source of the data of this study was the eighth grade students of SMP N 2 Padang in science learning, in the form of a questionnaire of validity, practicality and effectiveness. The results of this study were found from the validity test of 3 aspects namely aspects of media, material and language. Next test the practicality of teacher responses and student responses. While the effectiveness test seen from the results of learning and student learning activities. The results of the average product validity got a value of 91.34% the category is very valid, the average practicality of student responses 89.7% category is very practical. The average practicality of teacher responses 75% practical category. While the effectiveness test results of student learning outcomes obtained an average of 81.05% effective category and the value of student activities 91.25% very effective category. Based on the above data it can be concluded that multimedia-based e-books on natural science learning are valid, practical, and effective in the learning process.